ESTUDO DO SISTEMA RADICULAR DO PESSEGUEIRO (Prunus persica BATSCH) - Inforzato, Romeu; Rigitano, Orlando; Barreto, Geraldo Benedito; Ojima, Mario; Scaranari, Helio JosÃ© (REVISTA DE AGRICULTURA, 2015)
ESTUDO DO SISTEMA RADICULAR DO PESSEGUEIRO (Prunus persica BATSCH)